Hardy's Poetry, 1860-1928 - Taylor, D. author. aut Link
XXXVIII, 222 p.
Keywords: Hardy insisted that his poetry steadily grew in skill and maturity. Hardy's Poetry, 1860-1928 traces this development. Gradually Hardy makes his lyric poem the model of a man's life: the way the lyric speaker forms his thoughts within the few moments of a reverie recapitulates the way a man has thought over a lifetime; the smaller interruption of the reverie portends the larger interruptions of life. This lyric model is supported by a distinctive imagery of visual patterns whose implications Hardy explores. These patterns come to symbolise the patterns of life and mind which crystallise over a lifetime and are belatedly revealed.